Manifestations in the Criminal Policy of Family-Related Laws - Hassan, Assist. Prof. Dr. Muhammad Rashid (Journal of Legal and Political Studies, 2018)
This article focuses on the critical aspects of criminal legislation process regarding the family, especially domestic violence .it examines the core questions of the legal interest in law making process concerning the family and we will elaborate the constitutionality of criminal law . we questions whether there is a necessity to have special law criminalizes matters it was criminalized in general criminal law .and this is one of the aspects of over criminalization .accordingly we conclude that the legislator needs to take rationality and constitutionality in law making process , due to this fact we shied lights on the gaps and critical matters in iraqi criminal legeslations especially the law of eradication of domestic violence which was passed by kurdish legislator in 2008 . generally we argues vigorously the importance of resolving these problems in this crucial space.
Keywords: criminal legislation; domestic violence; constitutionality in law; criminalization